Efficacy and safety of tacrolimus in patients with rheumatoid arthritis – A systematic review and meta-analysis. Issue 1 (2nd January 2021) - Kaneko, Yuko; Kawahito, Yutaka; Kojima, Masayo; Nakayama, Takeo; Hirata, Shintaro; Kishimoto, Mitsumasa; Endo, Hirahito; Seto, Yohei; Ito, Hiromu; Nishida, Keiichiro; Matsushita, Isao; Kojima, Toshihisa; et al.
Abstract: Objectives: To evaluate the efficacy and safety of tacrolimus in adult patients with rheumatoid arthritis (RA) by using the GRADE approach. Methods: We searched PubMed, Japana Centra Revuo Medicina Web (Ichu-shi web), and the Cochrane Database of Systematic Reviews. Articles fulfilling the predefined inclusion criteria were appraised and used for meta-analysis. The primary outcomes were American College of Rheumatology 20 (ACR20) and serum creatinine elevation. Other outcomes included ACR50, ACR70, changes in C-reactive protein, modified Health Assessment Questionnaire Disability Index, gastrointestinal disorders, metabolic and nutritional disorders, and infections and infestations. Results: We identified five randomized controlled studies, four of which compared tacrolimus to placebo and were included in the meta-analysis. The risk ratio of ACR20 achievement was 1.71 (95% confidence interval [CI] 1.20–2.42) for 1–2 mg/day and 2.30 (95% CI 1.79–2.96) for 3 mg/day. The risk ratio of creatinine elevation was 1.95 (95% CI 1.18–3.23) for 1–2 mg/day and 3.81 (95% CI 2.43–5.99) for 3 mg/day. Conclusion: Tacrolimus is effective with acceptable safety in the management of RA.